1985
DOI: 10.1109/tit.1985.1056993
|View full text |Cite
|
Sign up to set email alerts
|

A lower bound on the average error of vector quantizers (Corresp.)

Abstract: A lower bound is proposed for the mean squared error of an n-dimensional vector quantizer with a large number of output points. Although no formal proof has been found, a plausible geometrical argument is given for believing that the bound is correct. The new bound is analogous to the Rogers bound for packing spheres, the Coxeter-Few-Rogers bound for covering space with spheres, and the Coxeter-Bo. . ro. . czky bound for packing spherical caps. It is significantly stronger than Zador's sphere bound for quantiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(16 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Fig. 2 summarizes the best classical lattices [43-46, 33, 47] along with Conway and Sloane's conjectured lower bound [44]. With "classical" we mean lattices for which the normalized second moment has been reported previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2 summarizes the best classical lattices [43-46, 33, 47] along with Conway and Sloane's conjectured lower bound [44]. With "classical" we mean lattices for which the normalized second moment has been reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…For d = 8 , the only local minimum found is 11 Among the "best known" lattices, only the ones in dimensions 1-3 have been proven optimal. 12 The values were computed using a series expansion of the recursive integral equation in [44]. 13 The 5-dimensional locally optimal lattice can be obtained as the intersection of D 6 * and a hyperplane perpendicular to the vector 1 1 1 1 1 1 , , , , , ( ) T .…”
Section: A the Best Lattices Foundmentioning
confidence: 99%
“…We combine this result with the welfare loss for the uniform distribution in one dimension to obtain a lower bound on the welfare loss in higher dimensions. Conway and Sloane (1985), the space-…lling advantage is SF (d) e 6 . Clearly, S f U ; d = 1, and DP f U ; f U ; d = 1, i.e., there are no shape and dependence advantages for the i.i.d.…”
Section: Lower Bound On Welfare Lossmentioning
confidence: 99%
“…[Zador 1982] developed an upper bound on C (d), or equivalently a lower bound on SF (d) using random quantization where the representation points are picked at random, and the partition is a Voronoi partition with respect to the set of representation points: [Conway and Sloane 1985] further showed that…”
Section: Advantages Of Vector Quantizationmentioning
confidence: 99%